Systematic review of Lonicerae Japonicae Flos: A significant food and traditional Chinese medicine - Zheng, Senwang; Liu, Songtao; Hou, Ajiao; Wang, Song; Na, Yexin; Hu, Jianhua; Jiang, Hai; Yang, Liu (Frontiers in Pharmacology, 2022)
Lonicerae Japonicae Flos has been used as a tea and medicine for more than 1,500 years. It has the functions of clearing heat, detoxification, and is often used to treat carbuncle, furuncle, throat arthralgia, erysipelas, heat-toxic blood dysentery, febrile fever. This paper summarizes the botany, ethnopharmacology, chemical composition and pharmacological action of Lonicerae Japonicae Flos from 1986 to 2022, and looks forward to the future research direction of Lonicerae Japonicae Flos. At present, the components isolated from Lonicerae Japonicae Flos include essential oils, organic acids, flavonoids, iridoids, saponins and other compounds. It has the effects of anti-inflammation, anti-virus, anti-bacteria, anti-oxidation, anti-tumor, protect liver and galltesticles, hypotensive, hypolipidemic, anti-thrombosis, anti-allergy, immune regulation and so on. It is often used in clinical treatment of diarrhea, hematochezia, febrile disease, exogenous wind-heat, and cold, swelling and toxin of carbuncle, sore throat and so on. The comprehensive evaluation of the quality of Lonicerae Japonicae Flos and the understanding of multi-target network pharmacology also need to be studied. As a kind of health food with high value, LJF is worthy of further promotion and development.